2014
DOI: 10.1513/annalsats.201408-389oc
|View full text |Cite
|
Sign up to set email alerts
|

An Empiric Antibiotic Protocol Using Risk Stratification Improves Antibiotic Selection and Timing in Critically Ill Children

Abstract: An empiric antibiotic protocol in the pediatric intensive care unit incorporating risk stratification for healthcare-associated infections resulted in increased appropriateness of empiric antibiotics and in decreased time to appropriate antibiotics in critically ill children with infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…[19,28,31,35,51,60,6366] Values for the percentage of compliance with guidelines are summarised in Table 5. CDS effects were measured as absolute percentage differences between CDS and intervention groups.…”
Section: Resultsmentioning
confidence: 99%
“…[19,28,31,35,51,60,6366] Values for the percentage of compliance with guidelines are summarised in Table 5. CDS effects were measured as absolute percentage differences between CDS and intervention groups.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a number of studies have shown that weight-based pre-written orders for vancomycin improve vancomycin dosing [12,13]. Introduction of order sets [groups of pre-written orders] have also been shown to improve antimicrobial use for severe sepsis [14], improve antimicrobial use in critically ill children [15], and increase timely discontinuation of post-operative antimicrobials [16].…”
Section: Background and Significancementioning
confidence: 99%
“…14 Similarly, there are protocols for the selection and administration of antibiotics, in both critically ill children and adults. 15,16 In each of these examples of a complex-accomplishing protocol, there is universal agreement that the condition should be treated and near-universal agreement on how that should be accomplished. Given that there is little equipoise on the issues (DKA should be treated with insulin, tailored antibiotics should be given for sepsis), the goal is not to standardize a difficult or controversial intervention.…”
Section: Protocol-based Medical Care: Advantages and Disadvantagesmentioning
confidence: 99%